XIV All-Russian Scientific-Practical Conference "Classical and Modern: The Problems of Studying and Teaching" (Yekaterinburg, 2009): A Review, Interviews, and Resolution (Филологический класс, 2009)
This review highlights the main issues discussed during the round tables and sections of the scientific-practical conference the teachers of literature "Classical and Modern", represented by the resolution of the conference as well as interviews with participants and the audience about the problems of contemporary literature and teaching literature in schools and universities.